Central venous pressure in the ventilated neonate. Issue 4 (April 1992) - Skinner, J R; Milligan, D W; Hunter, S; Hey, E N
Abstract : As there is no other measurement of right ventricular preload, central venous pressure (CVP) measurement provides unique and important haemodynamic information. CVP is not measured routinely in neonatology and there is a shortage of data in the ventilated neonate. CVP was measured in 62 ventilated neonates. Thirteen had respiratory disorders (28-42 weeks' gestation, birth weight 860-4390 g) and 49 had congenital heart disease (birth weight 1600-4500 g, age 0.5-30 days). Data from other case reports are also presented. In the babies with respiratory distress, a value of zero was associated with clinical evidence of hypovolaemia and negative values, common in the unventilated neonate, did not occur in those who were ventilated. Values over 7 mm Hg were found in babies with evidence of myocardial dysfunction or persistent fetal circulation but were also found with transmitted high intrathoracic pressure, such as with pneumothorax. In the babies with congenital heart disease, values mostly lay between 4 and 8 mm Hg. Values outside this range, particularly above 8 mm Hg, were usually associated with profound metabolic acidosis, suggesting circulatory failure. While the main use of CVP measurement is in trend analysis, this report suggests that single measurements can be of value, though correct interpretation will depend on the context in which they are made.